Factors Affecting Community Vaccination Perception as An Effort to Prevent Covid-19 - Ika Rahmawati; Putri Kristyaningsih (University of Muhammadiyah Malang, 2022)
Introduction: Covid-19 is an infectious disease that can prevent by vaccination. Covid-19 is a health problem that, if not handled properly, can cause the death of the sufferer. The vaccination program for Covid-19 is a focus carried out throughout the world. WHO stated that a high commitment is needed so that the distribution of the Covid-19 vaccine can be carried out evenly. The Indonesian government also participated in the success of the Covid-19 vaccination program. The vaccination program is a preventive effort carried out so that the community has immunity against Covid-19 However, in the implementation of the Covid-19 vaccination program, there are still those who agree and some who still disagree. People still have doubts administration of this vaccine, and there are even those who doubt the efficacy of the Covid-19 vaccine. Some things that cause people to disagree with the Covid-19 vaccination program are their fright of the vaccine ingredients. Community understanding about the importance of vaccines giving must be increased. Objectives: The purpose of this study was to find out how people perceive the Covid-19 vaccine as an effort to prevent Covid-19. Methods: The design in this study is cross-sectional. The sampling technique used is purposive sampling with a total sample of 153 respondents. This study uses google form as a measuring tool. The bivariate analysis uses contingency coefficients. Multivariate analysis using multiple logistic regression tests with a significant value of 0,05. Results: The results showed that the influencing factors that influenced community perceptions of the Covid-19 vaccine as an effort to prevent Covid-19 were the government's fear of the ingredients of the vaccine (p=0,016), the fear that the vaccine was not halal (0,023), anxiety about the side effects of the vaccine (p=0,014), anxious about news about Covid-19 (0,022), and fear of injections (0,027). The logistic regression analysis showed that anxiety about the side effects of giving the vaccine was the dominant factor influencing community perception of the Covid-19 vaccine with p=0,003. Conclusions: The government was expected to continuously support the vaccination program to prevent Covid- 19. Vaccination was expected to increase the body's immunity.